1985
DOI: 10.1002/art.1780281110
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive evaluation of cardiac dysrhythmias, and their relationship with multisystemic symptoms, in progressive systemic sclerosis patients

Abstract: Fifty‐three patients (34 who had diffuse scleroderma, and 19 who had CREST syndrome [calcinosis, Raynaud's phenomenon, esophageal dysmotility, sclerodactyly, and telangiectasias]) were studied by noninvasive procedures, including resting electrocardiogram (ECG), continuous 24‐hour Holter ECG monitoring, M‐mode echocardiography, and 2‐dimensional echocardiography. Only 22 patients (42%) had abnormalities such as conduction defects, supraventricular or ventricular arrhythmias, or ST‐T changes detected on resting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
4

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 25 publications
(11 reference statements)
2
38
0
4
Order By: Relevance
“…Indeed, anti-Scl70 is correlated with a severe outcome and has a negative prognostic significance, since it seems to be correlated with alterations in the cardiac rhythm in sclerodermic patients [28]. Indeed, anti-Scl70 is correlated with a severe outcome and has a negative prognostic significance, since it seems to be correlated with alterations in the cardiac rhythm in sclerodermic patients [28].…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, anti-Scl70 is correlated with a severe outcome and has a negative prognostic significance, since it seems to be correlated with alterations in the cardiac rhythm in sclerodermic patients [28]. Indeed, anti-Scl70 is correlated with a severe outcome and has a negative prognostic significance, since it seems to be correlated with alterations in the cardiac rhythm in sclerodermic patients [28].…”
Section: Discussionmentioning
confidence: 98%
“…Both supraventricular and life-threatening ventricular arrhythmias are seen in SSc [60,61,[65][66][67]. The etiology is unknown but it is suspected that myocardial fibrosis leads to conduction abnormalities rather than directing causing conduction system disease [60].…”
Section: Arrhythmiasmentioning
confidence: 99%
“…The etiology is unknown but it is suspected that myocardial fibrosis leads to conduction abnormalities rather than directing causing conduction system disease [60]. The presence of these arrhythmias is high enough that many suggest screening for arrhythmias; with a 24-hour holter [59,66]; even in asymptomatic SSc patients. There is no evidence showing decreased mortality from ventricular arrhythmia with use of antiarrhythmic drugs in SSc.…”
Section: Arrhythmiasmentioning
confidence: 99%
“…Some studies observed no significant difference in the nature and severity of cardiac involvement between the two forms of scleroderma (4,5). However, severe cardiac involvement, such as acute onset of cardiac congestion, has so far rarely been described in patients with ISSc (6).…”
Section: Introductionmentioning
confidence: 99%